중국의 소셜미디어 라이브커머스에서 뷰티인플루언서 속성과 구매의도의 관계 - 김상조(Sang-Jo Kim); 정선미(Seon-Mi Jung); 양가이(Jia-Yi Yang) (무역연구, 2024)
Purpose – The goal of this study was to analyze how the characteristics of beauty influencers in live commerce affect the purchase intention of users through satisfaction and trust. Design/Methodology/Approach – This study classified the attributes of beauty influencers active in live commerce into authenticity, expertise, entertainment, attractiveness, and interactivity. The survey was conducted using Questionnaire, a Chinese survey platform. The survey target was Chinese adults under the age of 40 with substantial experience watching beauty influencer live commerce on social media. The survey period was conducted from December 1 to December 25, 2023. SPSS 27 and AMOS 24 were used to analyze the data. Findings – The result of this study are as follows. First, among the influencer attributes of social media live commerce, authenticity, expertise, attractiveness, and interactivity all had a significant positive effect on consumer satisfaction. Second, among the influencer attributes of social media live commerce, authenticity, expertise, and interactivity had a positive effect on broadcast trust. Third, satisfaction and trust with influencer broadcasts of social media live commerce had a significant effect on purchase intention. Research Implications – The results of the study showed that in China's beauty live commerce, the attractiveness or entertainment of influencers did not have a significant effect on broadcast trust or satisfaction. The result of this studies can help with the distribution and messaging strategies of Korean K-beauty-related companies entering the Chinese beauty market. KCI Citation Count: 0